Around the wall: Musealizzazione dell'area archeologica di fronte al Muro Occidentale - Fabbrizzi, Fabio (AND Rivista di architetture, città e architetti, 1970)
Not all projects are the same. Not only because of the different results that can be achieved but precisely because of what they manage to set in motion during the various stages of their development.